Technical Efficiency of Combine Harvester in Mindugading Village - Dwi Kusuma Wati; Hamidah Hendrarini; Risqi Firdaus Setiawan (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
Farmers' adjustments in combining harvesters cause rice production to fluctuate yearly. This research intends to analyze factors impacting rice production and the degree of technical proficiency of rice farming using a combine harvester in Mindugading village. The study was accomplished in Mindugading Village, Tarik District, Sidoarjo Regency, East Java, from February to March 2024. A total of 53 farmers were sampled using a simple random sampling technique in this study. The variables utilized in this research are land area, seeds, labor, fertilizer, pesticides, and rental costs. The analytical method utilized in this research applies a parametric approach through models of Stochastic Frontier Analysis. The first stage uses the Ordinary Least Square (OLS) method, and the second uses the Maximum Likelihood Estimation (MLE) method. This analysis was carried out with the assistance of Frontier Stochastic 4.1 software. The research outcomes reveal that rice production is affected by land area, fertilizer, seeds, and rental costs. The value of the combine harvester's technical efficiency is 0.87.